Responsible innovation by social entrepreneurs: an exploratory study of values integration in innovations. Issue 2 (4th May 2019) - Lubberink, Rob; Blok, Vincent; van Ophem, Johan; Omta, Onno
ABSTRACT: The upcoming concept of responsible innovation seems to gain foothold in Europe and beyond, but it still remains unknown how it can be implemented in the business context. This article explores how social entrepreneurs integrate values into their de facto responsible innovations, and provides empirically informed strategies to develop, implement and scale these innovations. It is based on an empirical investigation of 42 case studies of best-practice social entrepreneurs. This empirical study shows that social entrepreneurs focus on creating direct socio-ethical value for their target beneficiaries. They coordinate collective stakeholder action to develop, implement and scale their systems-changing solutions. And their bottom-up innovations are evaluated and scaled for impact. Ultimately, institutional support is sought to create top-down systems change. This article suggests a synthesised model of integrated strategies for responsible innovation that also covers implementation and scaling of innovation.